Socialization of Intellectual Property Rights (IPR) to coffee shop business actors in Denpasar City - Nuning Indah Pratiwi; I Wayan Putu Suparta; I Wayan Joniarta (Community Empowerment, 2023)
The Office of Cooperatives and MSMEs in Denpasar City is a human resource development agency and training center for human resources. The role of this Office is to provide training in encouraging young employees and entrepreneurs to develop skills, enthusiasm and critical thinking to develop MSME products. This community service activity aims to improve the quality of human resources, especially in the aspect of the urgency of Intellectual Property Rights (IPR) for coffee shop entrepreneurs in Denpasar City. The result of this program is an increase in knowledge about IPR and concrete actions in registering intellectual property for the products and brands of businesses that are initiated.